2000
DOI: 10.1200/jco.2000.18.3.463
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Omeprazole or Ranitidine Versus Placebo in the Prevention of Chemotherapy-Induced Gastroduodenal Injury

Abstract: Omeprazole is effective in preventing chemotherapy-induced gastroduodenal injury. Ranitidine is effective in reducing the frequency of ulcers and upper gastrointestinal symptoms but is not effective in preventing the global endoscopic worsening caused by chemotherapy. The different efficacy of omeprazole and ranitidine can be explained by their different pharmacodynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 21 publications
2
29
0
2
Order By: Relevance
“…No severe complications were reported in any treatment arm. A second study, enrolling 238 patients with similar characteristics, compared the administration of Omeprazole 20 mg daily with Ranitidine 300 mg daily, with placebo (Sartori et al, 2000). Again, the results of Omeprazole were significantly better than placebo both in terms of endoscopic findings and of symptoms' control.…”
Section: Chemotherapy-induced Gastric Damagementioning
confidence: 99%
See 1 more Smart Citation
“…No severe complications were reported in any treatment arm. A second study, enrolling 238 patients with similar characteristics, compared the administration of Omeprazole 20 mg daily with Ranitidine 300 mg daily, with placebo (Sartori et al, 2000). Again, the results of Omeprazole were significantly better than placebo both in terms of endoscopic findings and of symptoms' control.…”
Section: Chemotherapy-induced Gastric Damagementioning
confidence: 99%
“…Endoscopically-documented mucosal damage was evident in nearly half of the patients after the second cycle in the non-Omeprazole arms. Some limitations of the two chemotherapy trials (Sartori et al, 1996(Sartori et al, , 2000, together with additional concerns, should be taken into account. First of all, gastric damage did not translate into clinically relevant consequences, such as bleeding, anemia, or perforation.…”
Section: Chemotherapy-induced Gastric Damagementioning
confidence: 99%
“…Two studies published by Sartori et al [13,14] showed that omeprazole and ranitidine reduced epigastric pain and decreased gastric and duodenal erosions.…”
Section: Management Of Gi Mucositismentioning
confidence: 98%
“…Traitement préventif [36] Traitement préventif mucite gastro-intestinale le sucralfate n'est pas recommandé pour réduire • les effets secondaires liés à la radiothérapie. Elle n'empêche pas la diarrhée aiguë chez les patients atteints de tumeurs malignes du bassin (exemple : métastases osseuses de cancer du sein) soumis à une radiothérapie externe.…”
Section: Recommandations Pour La Mucite Gastro-intestinaleunclassified